Comparative Risk Return Analysis of Nepal Stock Market with Selected Banking Stocks in Nepal - Thapa, Narad Kumar (Nepal Journal of Multidisciplinary Research, 2023)
The Nepalese stock market, specifically concentrating on three commercial banks listed on the Nepal Stock Exchange Limited. The paper aims to analyze the risk and return associated with investing in common stocks in the Nepalese stock market, focusing on three commercial banks. Secondary data is gathered from various sources, including the NEPSE website, prior studies, publications by the NRB (Nepal Rastra Bank), commercial banks' websites, and the SEBON (Securities Board of Nepal) website. The paper employs scientific analysis techniques on quantitative data. Different methods, such as correlation, regression, and descriptive statistics, are used to test hypotheses and investigate the risk-return trade-off in the Nepalese stock markets. The analysis is based on the results of the sample banks' risk and return analysis, utilizing historical data from their most recent five fiscal years, spanning from FY-2017/18 to FY-2021/22. The abstract concludes that the three commercial banks examined in the study are characterized by high risk and variable rates of return.